2018
DOI: 10.3390/ph11040109
|View full text |Cite
|
Sign up to set email alerts
|

New Perspectives in Iron Chelation Therapy for the Treatment of Neurodegenerative Diseases

Abstract: Iron chelation has been introduced as a new therapeutic concept for the treatment of neurodegenerative diseases with features of iron overload. At difference with iron chelators used in systemic diseases, effective chelators for the treatment of neurodegenerative diseases must cross the blood–brain barrier. Given the promissory but still inconclusive results obtained in clinical trials of iron chelation therapy, it is reasonable to postulate that new compounds with properties that extend beyond chelation shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
99
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(100 citation statements)
references
References 197 publications
1
99
0
Order By: Relevance
“…The encouraging results obtained for this CA prompted the development of other clinical trials with Deferiprone. A search in https://clinicaltrials.gov indicated four ongoing or finished tests of this molecule for the treatment of PD, as also recently reported by Nuñez and Chana-Cuevas [79].…”
Section: Metal Chelation Therapy In Parkinson's Diseasementioning
confidence: 63%
See 1 more Smart Citation
“…The encouraging results obtained for this CA prompted the development of other clinical trials with Deferiprone. A search in https://clinicaltrials.gov indicated four ongoing or finished tests of this molecule for the treatment of PD, as also recently reported by Nuñez and Chana-Cuevas [79].…”
Section: Metal Chelation Therapy In Parkinson's Diseasementioning
confidence: 63%
“…Despite these toxicity reports, the occurrence of a metal ion dyshomeostasis in PD has suggested to also employ MCT for the therapy of this disease and of other NDs such as corticobasal degeneration, the Westfal variant of Huntington's disease, Alzheimer's disease, Friedreich's ataxia, pantothenate kinase-associated neurodegeneration, and other neuropathologies associated with brain metal overload [12,24,78,79]. In these cases, MCT was also referred to as "metal targeting", "metal attenuating" or "metal protein attenuating" [41,80,81], in order to underline the differences occurring when MCT is employed in NDs instead of in metal overloads.…”
Section: Metal Chelation Therapy In Parkinson's Diseasementioning
confidence: 99%
“…5 Aberrant iron accumulation in the brain has been reported to be associated with neurodegenerative diseases, such as Alzheimer's diseases (AD), Parkinson's diseases (PD), and Huntington diseases. [6][7][8] Oxidative stress resulting from the accumulated iron triggers neuronal death leading to neurodegeneration; 9 iron being associated with production of reactive oxygen species (ROS), which injure cellular membranes, proteins and deoxyribonucleic acid (DNA). 10 Divalent metal transporter 1 (DMT1/SLC11A2) is an H + -driven multi-metal transporter responsible for transmembrane iron transport; 11 in particular DMT1 has a principle role in transporting iron into the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Different studies demonstrated deferiprone's ability to chelate not only iron but also copper, aluminum and zinc [73], reducing their free radical catalytic activity [74]. Moreover, multifunctional iron/copper chelating agents have been evaluated even if their clinical translation has not yet progressed [75].…”
Section: Parkinson's Diseasementioning
confidence: 99%